2021
DOI: 10.1172/jci132727
|View full text |Cite|
|
Sign up to set email alerts
|

mTOR-dependent translation amplifies microglia priming in aging mice

Abstract: Microglia maintain homeostasis in the brain. However, with age, they become primed and respond more strongly to inflammatory stimuli. We show here that microglia from aged mice upregulated mammalian target of rapamycin (mTOR) complex 1 signaling regulating translation, as well as protein levels of inflammatory mediators. Genetic ablation of mTOR signaling showed a dual, yet contrasting effect on microglia priming: it caused an NF-kB-dependent upregulation of priming genes at mRNA level; however, mice displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 96 publications
(102 reference statements)
4
56
0
3
Order By: Relevance
“…Notably, many of the monocytic inflammatory pathways we found to be upregulated in stress-primed myeloid cells were also observed in western diet-trained myeloid cells, including type I IFN response genes and the IL-6 pathway ( Christ et al, 2018 ). Metabolic signaling has also been shown to be an important regulator of inflammatory memory responses in primed myeloid cells, resulting in a sensitized state with a lower threshold for activation, leading to an exaggerated inflammatory response ( Crişan et al, 2017 ; Keane et al, 2021 ; Ullevig et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many of the monocytic inflammatory pathways we found to be upregulated in stress-primed myeloid cells were also observed in western diet-trained myeloid cells, including type I IFN response genes and the IL-6 pathway ( Christ et al, 2018 ). Metabolic signaling has also been shown to be an important regulator of inflammatory memory responses in primed myeloid cells, resulting in a sensitized state with a lower threshold for activation, leading to an exaggerated inflammatory response ( Crişan et al, 2017 ; Keane et al, 2021 ; Ullevig et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that the mechanistic target of rapamycin (mTOR) signaling pathway is a powerful regulator of the microglial inflammatory response, including LPS-induced Il1b expression. 36 Therefore, mTOR kinase activation was examined in siCtrl and si Ezh2 BV2 cells following coculture with H3-K27M SF8628 DIPG cells or wild-type H3 SF188 pHGG cells. Indeed, we found increased phosphorylation, of one of the main substrates of mTOR, S6 ribosomal protein, suggesting an activation of the mTOR pathway in si Ezh2 BV2 cells consistent with an increased pro-inflammatory phenotype 36 ( Figure 4H ).…”
Section: Resultsmentioning
confidence: 99%
“… 36 Therefore, mTOR kinase activation was examined in siCtrl and si Ezh2 BV2 cells following coculture with H3-K27M SF8628 DIPG cells or wild-type H3 SF188 pHGG cells. Indeed, we found increased phosphorylation, of one of the main substrates of mTOR, S6 ribosomal protein, suggesting an activation of the mTOR pathway in si Ezh2 BV2 cells consistent with an increased pro-inflammatory phenotype 36 ( Figure 4H ). Overall, these observations suggested that si Ezh2 microglia may exhibit anti-tumoral properties and therefore we decided to investigate this possibility using several functional assays to measure anti-tumoral capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Aged microglia have also been described as ‘primed’ [ 62 , 70 , 71 ], whereby the threshold for the microglia to be triggered to an activated state is substantially lower, and this has been suggested to be under the control of mTOR-dependent translation [ 72 ]. Interestingly, mTOR signalling has been reported to be impaired by TREM2 deficiency [ 69 ].…”
Section: Microglial States and Functionsmentioning
confidence: 99%